2022
DOI: 10.1073/pnas.2117940119
|View full text |Cite
|
Sign up to set email alerts
|

Middle Eastern and North African Americans may not be perceived, nor perceive themselves, to be White

Abstract: People of Middle Eastern and North African (MENA) descent are categorized as non-White in many Western countries but counted as White on the US Census. Yet, it is not clear that MENA people see themselves or are seen by others as White. We examine both sides of this ethnoracial boundary in two experiments. First, we examined how non-MENA White and MENA individuals perceive the racial status of MENA traits (external categorization), and then, how MENA individuals identify themselves (self-identification). We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 45 publications
0
62
0
Order By: Relevance
“…Such equity-oriented strategies in the United States are limited due to long-standing obfuscation of data collection on race and ethnicity, across federal agencies including the NIH, that systematically invisibilize the MENA community. Although evidence demonstrates that MENA Americans experience significant identity-related discrimination and may not actually identify as White, they remain categorized as non-Hispanic Whites in U.S. administrative data ( Maghbouleh et al, 2022 ). This renders MENA people ineligible or otherwise excluded from the vast majority of health-related and social equity initiatives for ethnic and racial minorities in the United States ( Abboud et al, 2019 ; Awad et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such equity-oriented strategies in the United States are limited due to long-standing obfuscation of data collection on race and ethnicity, across federal agencies including the NIH, that systematically invisibilize the MENA community. Although evidence demonstrates that MENA Americans experience significant identity-related discrimination and may not actually identify as White, they remain categorized as non-Hispanic Whites in U.S. administrative data ( Maghbouleh et al, 2022 ). This renders MENA people ineligible or otherwise excluded from the vast majority of health-related and social equity initiatives for ethnic and racial minorities in the United States ( Abboud et al, 2019 ; Awad et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, MENA Americans are counted as White in the US federal race/ethnicity standards and within the NIH, thereby excluding them from discussions on disparities research, practice, and policy. There are increasing calls to disaggregate data on MENA Americans ( Abboud et al, 2019 ; Awad et al, 2022 ; Maghbouleh et al, 2022 ), an approach already adopted by the American Medical Association; “MENA” is currently under consideration by the U.S. Office of Management and Budget to be added as an identity category to the federal race/ethnicity standards. Across the border, however, in Canada, members of this community are counted as non-White “visible minorities” in governmental data collection under the terminology “Middle Eastern” and the subcategories “Arab” (by population size, for example, Lebanese, Algerian, or Moroccan Canadians) and “West Asian” (by population size, for example, Afghan, Armenian, or Iranian).…”
mentioning
confidence: 99%
“…In a study using an online, crowdsourcing platform to obtain a nonprobability of sample respondents and conduct a factorial experiment, Maghbouleh found that respondents who identify as MENA change their responses based on survey options, with 88% identifying as MENA alone when given the option. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Cautions When Using Race and Ethnicity in Administrative Claims Data Sets Human Services data collection standards categorize people of Middle Eastern descent as White, despite evidence that people of Middle Eastern descent may not be perceived or perceive themselves to be White. 9 Administrative claims data sets are a valuable research resource. Massive sample sizes and rapidly updated data sets can facilitate the timely investigation of key research questions, but there is a need to actively evaluate and enhance their quality for research.…”
Section: Jama Health Forum | Viewpointmentioning
confidence: 99%